2016
DOI: 10.1128/aac.02788-15
|View full text |Cite
|
Sign up to set email alerts
|

First Characterization of CTX-M-15-Producing Escherichia coli Strains Belonging to Sequence Type (ST) 410, ST224, and ST1284 from Commercial Swine in South America

Abstract: T he rapid spread of the bla CTX-M-15 gene, which encodes the currently most widely distributed extended-spectrum ␤-lactamase (ESBL) enzyme in Gram-negative bacteria, is a global challenge to human and veterinary medicine. In this context, foodproducing animals have acquired an important role as reservoirs for CTX-M-15-producing bacteria, which can be transmitted to the community (1, 2). In this report, we describe for the first time the isolation of CTX-M-15-producing Escherichia coli in commercial swine in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 17 publications
3
19
0
3
Order By: Relevance
“…Notably, both ST10 and ST224 previously demonstrated their capacity for nosocomial infections and the spread of these sequence types between horses and potentially, to their human handlers [14,18,19]. In addition to being recovered from horses [14], ST224 was isolated from humans [11], swine [42], bovines [47], birds [44], and in this study, from a donkey. ST167 E. coli was isolated from humans, cattle, swine, wild birds [34,46,48], turkey meat [43], and horses [49].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Notably, both ST10 and ST224 previously demonstrated their capacity for nosocomial infections and the spread of these sequence types between horses and potentially, to their human handlers [14,18,19]. In addition to being recovered from horses [14], ST224 was isolated from humans [11], swine [42], bovines [47], birds [44], and in this study, from a donkey. ST167 E. coli was isolated from humans, cattle, swine, wild birds [34,46,48], turkey meat [43], and horses [49].…”
Section: Discussionmentioning
confidence: 58%
“…ST410, which was identified in 3 of the 13 E. coli isolates, has also been described as an emerging high-risk E. coli with potential international implications [37]. ST410 was previously isolated from humans [38,39], canines, felines [40], swine, poultry, cattle [41][42][43], as well as birds [44]. E. coli ST10, identified in two of the 13 isolates, was recovered from humans, turkey meat, chickens, swine, cattle [45,46], and horses [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Silva et al reported eight isolates obtained in 2012 also in the same state from pig fecal swabs resistant to third-and fourth-generation cephalosporins, associated with the occurrence of the ESBL encoding gene bla CTX-M-15 . These isolates were also resistant to ciprofloxacin, enrofloxacin, norfloxacin, tetracycline, sulfonamide-trimethoprim, and gentamicin, being sensitive only to amikacin, cephamycins, and carbapenems [87].…”
Section: E Colimentioning
confidence: 99%
“…Sequences correlating to IncA/C2, IncFIA, IncFIB, IncFII, IncI1, IncQ1, IncX3, IncX4, Col(BS512) and Col156 plasmids were identified, with incompatibility groups IncFIA and IncFIB being present in all isolates (Table 12). The widespread emergence of the blaCTX-M-15 gene, which is frequently interrelated with TEM-1, OXA-1 and aac(6')-Ib-cr, was mainly linked to IncF replicons (Carattoli, 2009 (Carattoli, 2009 andSilva et al, 2016), all of which were in harmony with this study's results (Table 6 and 11). Furthermore, ECC 167 and ECC 194 carried the pBS512_2 plasmid, which is linked to type III secretion system (Villa et al, 2010).…”
Section: Plasmidssupporting
confidence: 83%
“…ST-1284 (CC10) E. coli isolates were CTX-M-15 producers (Novais et al, 2012), which was similar to ECC 167 (ST-1284) (Table 11). E. coli ST-1284 was previously isolated from raw milk in Algeria (Yaici et al, 2016) and commercial swine in Brazil (Silva et al, 2016). However, to the best of our knowledge, this is the first isolation and Korea (human) .…”
Section: Antibiotic Resistancementioning
confidence: 92%